Estimated Cancer Incidence in Brazil, 2023-2025 - Santos, Marceli de Oliveira (2023)
Introduction: Cancer is a worldwide public health problem, in the last decade there was an increase of 20% of the incidence and more than 25 million new cases are expected by 2030. Estimates of the number of new cancer cases are a powerful tool to support public policies and rational allocation of resources to fight cancer. Cancer surveillance is paramount for planning, monitoring and evaluating cancer control programs. Objective: To estimate and to describe the incidence of cancer in the country, geographic regions, states, Federal District and capitals, by sex, for the 2023-2025 period. Method: Cancer mortality and incidence information were extracted from the Mortality Information System and from Population-Based Cancer Registries. The number of new cases and their respective incidence rates were estimated by time-linear prediction models or by the incidence and mortality ratio. Results: 704,000 new cases of cancer are expected for the triennium 2023-2025. Except for nonmelanoma skin cancer, 483,000 new cases will occur. Female breast cancer and prostate cancer were the most frequent with 73,000 and 71,000 new cases, respectively, followed by colorectal cancer (45,000), lung (32,000) and stomach (21,000), and cervical cancer (17,000). Conclusion: In Brazil, due to its continental dimensions and heterogeneity both in terms of population and territory, the incidence profile reflects the diversity of geographic regions, and patterns similar to developed and developing countries.